2006
DOI: 10.1037/h0088911
|View full text |Cite
|
Sign up to set email alerts
|

Look, up in the sky! Using superheroes in play therapy.

Abstract: Fantasy and fantasy play are key elements in healthy child development, and as such, are potentially important resources for play therapy. The multi-media genre of superhero mythology has long provided children (and adults) with rich fantasies serving a number of important developmental functions, including emotional release, a sense of power, instillation of hope, a resource for problem solving and identity formation. Whether Captain America, Superman, Spiderman, the Justice League of America, X-Men, or Pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Taylor and Carlson () found that children with pretend identities, like children with invisible friends and with personified objects, scored higher on theory of mind tasks than children who did not engage in any type of role‐play, but pretend identities have mostly been investigated separately from research on imaginary companions. For example, there are several studies that explore the positive themes in superhero pretending (e.g., fighting against injustice), as well as the potential for this type of role‐play to be helpful in clinical settings (Boyd, ; Martin, ; Rubin & Livesay, ).…”
Section: Introductionmentioning
confidence: 99%
“…Taylor and Carlson () found that children with pretend identities, like children with invisible friends and with personified objects, scored higher on theory of mind tasks than children who did not engage in any type of role‐play, but pretend identities have mostly been investigated separately from research on imaginary companions. For example, there are several studies that explore the positive themes in superhero pretending (e.g., fighting against injustice), as well as the potential for this type of role‐play to be helpful in clinical settings (Boyd, ; Martin, ; Rubin & Livesay, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in 1941 Bender and Lourie examined three children's neurotic episodes or negative behaviour and concluded that comics can function ' as a means of helping them solve the individual and sociological problems appropriate to their own lives' (Bender and Lourie, 1941: 550). More recently, the powers of comic-book characters, especially superheroes, have been invoked as ways of reaching traumatised children and helping therapists construct narratives for the healing process (Rubin, 2005;Kaplan-Weinger, 2012;Rubin and Livesay, 2006;Taransaud, 2013;Fradkin, 2016). The author of a book on the workings of the Tavistock Clinic itself also supports the therapeutic use of comics because a child can ' enjoy this format, perhaps because the stylised form and the slightly mocking quality seems to tone down any raw emotions which might otherwise be revealed' (Taylor, 1999: 23).…”
Section: Comics and Mental Healthmentioning
confidence: 99%
“…Each family member is asked to identify a favorite existing superhero and will then be asked to create their own personal superhero (adapted from Rubin & Livesay, 2006). They are asked to draw a picture of their superhero (or find the figure among the miniatures if available) and list their superpower/superpowers, important resources, and strengths/skills.…”
Section: Inclusive Techniquesmentioning
confidence: 99%